Synthetic surgical meshes used in abdominal wall surgery: Part I—materials and structural conformation. Issue 3 (16th December 2015) - Todros, S.; Pavan, P. G.; Natali, A. N.
Abstract: Surgical implants are commonly used in abdominal wall surgery for hernia repair. Many different prostheses are currently offered to surgeons, comprising permanent synthetic polymer meshes and biologic scaffolds. There is a wide range of synthetic meshes currently available on the market with differing chemical compositions, fiber conformations, and mesh textures. These chemical and structural characteristics determine a specific biochemical and mechanical behavior and play a crucial role in guaranteeing a successful post‐operative outcome. Although an increasing number of studies report on the structural and mechanical properties of synthetic surgical meshes, nowadays there are no consistent guidelines for the evaluation of mechanical biocompatibility or common criteria for the selection of prostheses. The aim of this work is to review synthetic meshes by considering the extensive bibliography documentation of their use in abdominal wall surgery, taking into account their material and structural properties, in Part I, and their mechanical behavior, in Part II. The main materials available for the manufacture of polymeric meshes are described, including references to their chemical composition, fiber conformation, and textile structural properties. These characteristics are decisive for the evaluation of mesh‐tissue interaction process, including foreign body response, mesh encapsulation, infection, and adhesion formation. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 689–699, 2017.